2019
DOI: 10.1002/jbt.22379
|View full text |Cite
|
Sign up to set email alerts
|

Neonicotinoid pesticides poorly interact with human drug transporters

Abstract: The interactions of six neonicotinoid pesticides and one neonicotinoid metabolite with drug transporters have been characterized in vitro. Acetamiprid, clothianidin, imidacloprid, nitenpyram, thiacloprid and its metabolite thiacloprid amide, and thiamethoxam, each used at 100 µM, did not impair activity of the efflux pumps P‐glycoprotein, multidrug resistance‐associated proteins, and breast cancer resistance protein. They also did not inhibit that of the uptake transporters OATP1B1, OATP1B3, OAT4, and MATE1, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Nevertheless, predictions by our combination of web tools were correlated for other pesticides such as tebufenozide and methoxyfenozide, described as P‐gp inhibitors by a previous study, [ 33 ] but also imidacloprid and nitenpyram reported in vitro to be P‐gp noninhibitors. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, predictions by our combination of web tools were correlated for other pesticides such as tebufenozide and methoxyfenozide, described as P‐gp inhibitors by a previous study, [ 33 ] but also imidacloprid and nitenpyram reported in vitro to be P‐gp noninhibitors. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 8–14 ] On the other hand, pesticides lindane, dieldrin, dimethoate, methomyl, aminocarb, chlorpropham and acetamiprid have been described as not inhibiting P‐gp. [ 15–19 ] Finally, endosulfan and diazinon remain ambiguous because studies have reported them either as a P‐gp inhibitor or not depending on the in vitro assay used. [ 13,15,16,20,21 ] The diversity of the approaches used, sometimes in association with methodologies of little relevance, could partially explain the discrepancies observed between the results of these various studies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to natural products, transporter-based interactions are also observed for environmental xenobiotics, including pesticides and persistent organic pollutants 126 . In vitro studies suggest that two widely used pesticides, namely neonicotinoids and pyrethroids, interact with both uptake and efflux transporters 127 , 128 . However, the concentrations of these pesticides required to inhibit transporters are much higher than their environmental concentrations, and their interactions with transporters are therefore unlikely to occur in humans.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…or are around 3 μM for endosulfan, phosalone, and propiconazole . Allethrin and tetramethrin IC 50 values for SLC transporters are from 2.6 μM (for OCT1 inhibition by allethrin) to 77.6 μM (for OAT3 inhibition by tetramethrin), and IC 50 of the neonicotinoid thiacloprid towards OAT3 and OCT2 activities are in the 20–60 μM range . Such concentrations are at least one order of magnitude higher than human plasma concentrations of most pesticides occurring in response to environmental or occupational exposures, which are commonly around the 1 nM to 0.5 μM range .…”
Section: Modulation Of Drug Transporter Activity By Pesticidesmentioning
confidence: 92%